Lifetime Assessment of InxGa1−xAs n‐Type Hetero‐Epitaxial Layers. Issue 17 (19th June 2022) - Hsu, P.-C. (Brent); Simoen, Eddy; Eneman, Geert; Merckling, Clement; Mols, Yves; Heyns, Marc
Abstract : Herein, the carrier lifetime in ≈5 × 10 16 cm −3 n‐doped In x Ga1− x As layers is studied by diode current–voltage analysis and by time‐resolved photoluminescence. Two sets of hetero‐epitaxial layers are grown on semi‐insulating InP or GaAs substrates. The first set corresponds with a constant In content p + n stack, while the second set has a fixed x = 0.53 for the n‐layer, while containing various extended defect densities by using a strain relaxed buffer with different x . This results in threading dislocation densities (TDDs) between ≈10 5 cm −2 and a few 10 9 cm −2 . It is shown that the overall trend of the recombination lifetime versus TDD can be described by a first‐order model considering a finite recombination lifetime value inside a dislocation core of 1 nm. For the generation lifetime, a strong electric‐field enhancement factor is found. Also, the residual strain in the n‐layer has an impact. Overall, the safe limit for TDD depends on the type of application and on the operation conditions (reverse diode bias). Abstract : Herein, the carrier lifetime in ≈5 × 10 16 cm −3 n‐doped In x Ga1− x As layers is studied by diode current–voltage analysis and by time‐resolved photoluminescence. Two sets of hetero‐epitaxial layers are grown on semi‐insulating InP or GaAs substrates. This results in threading dislocation densities (TDDs) between ≈10 5 cm −2 and a few 10 9 cm −2 . It is shown that the overall trend of the recombination lifetime versus TDD can be described by a first‐order model considering a finite recombination lifetime value inside a dislocation core of 1 nm. Overall, the safe limit for TDD depends on the type of application and on the operation conditions (reverse diode bias).